SalvGlandDx - a comprehensive salivary gland neoplasm specific next generation sequencing panel to facilitate diagnosis and identify therapeutic targets - Freiberger, Sandra N; Brada, Muriel; Fritz, Christine; Höller, Sylvia; Vogetseder, Alexander; Horcic, Milo; Bihl, Michel; Michal, Michal; Lanzer, Martin; Wartenberg, Martin; Borner, Urs; Bode, Peter K; et al. (Neoplasia (New York, N.Y.), 2021)
Diagnosis of salivary gland neoplasms is often challenging due to their high morphological diversity and overlaps. Several recurrent molecular alterations have been described recently, which can serve as powerful diagnostic tools and potential therapeutic targets (e.g. NTRK or RET fusions). However, current sequential molecular testing can be expensive and time consuming. In order to facilitate the diagnosis of salivary gland neoplasms, we designed an all-in-one RNA-based next generation sequencing panel suitable for the detection of mutations, fusions and gene expression levels (including NR4A3) of 27 genes involved in salivary gland neoplasms. Here we present the validation of the "SalvGlandDx" panel on FFPE histological specimen including fine needle aspiration (FNA) cell block material, against the standard methods currently used at our institution. In a second part we describe selected unique cases in which the SalvGlandDx panel allowed proper diagnosis and new insights into special molecular characteristics of selected salivary gland tumors. We characterize a unique salivary gland adenocarcinoma harboring a ZCCHC7-NTRK2 fusion, a highly uncommon spindle cell and pseudoangiomatoid adenoid-cystic carcinoma with MYBL1-NFIB fusion, and a purely oncocytic mucoepidermoid carcinoma, whereas diagnosis could be made by detection of a CRTC3-MAML2 rearrangement on the cell block specimen of the FNA. Further, a rare case of a SS18-ZBTB7A rearranged low-grade adenocarcinoma previously described as potential spectrum of microsecretory adenocarcinoma, is reported. In addition, features of six cases within the spectrum of polymorphous adenocarcinoma / cribriform adenocarcinoma of salivary gland including PRKD1 p.E710D mutations and novel fusions involving PRKAR2A-PRKD1, SNX9-PRKD1 and ATL2-PRKD3, are described.
Keywords: Testing; mutace; nádory slinných žláz; Cell Line, Tumor; Comprehensive; hybridizace in situ fluorescenční; Neoplasm Grading; High-Throughput Nucleotide Sequencing; Neoplasm Staging; biopsie; imunohistochemie; fúzní onkogenní proteiny; stanovení celkové genové exprese; Gene Expression Profiling; Oncogene Proteins, Fusion; Salivary Gland Neoplasms; Molecular; lidé; Immunohistochemistry; stupeň nádoru; Humans; FNA; vysoce účinné nukleotidové sekvenování; In Situ Hybridization, Fluorescence; Biopsy; Mutation; nádorové buněčné linie; Biomarkers, Tumor; staging nádorů; nádorové biomarkery; Salivary gland neoplasm